2021
DOI: 10.1038/s41598-021-94631-5
|View full text |Cite
|
Sign up to set email alerts
|

High triglyceride-glucose index is associated with early recurrent ischemic lesion in acute ischemic stroke

Abstract: The triglyceride-glucose (TyG) index has been associated with various metabolic, cardiovascular, and cerebrovascular diseases. We evaluated the association between the TyG index and early recurrent ischemic lesions (ERILs) in patients with acute ischemic stroke (AIS). We included consecutive patients diagnosed with AIS between 2010 and 2016. ERILs were defined as new diffusion-weighted imaging lesions outside the initial symptomatic lesion area. The TyG index was calculated using the following formula: log sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
44
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 34 publications
5
44
1
Order By: Relevance
“…It is associated with arterial stiffness 41 , increased risk of cardiovascular disease and worse post-percutaneous coronary intervention outcomes 19 . In stroke, the TyG index has been associated with increased risk of stroke 22 , in-hospital mortality in critically-ill stroke 24 , and early recurrent ischemic lesions 25 . Baseline TyG index has been associated with increased mortality and neurologic deterioration in ischemic stroke 23 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is associated with arterial stiffness 41 , increased risk of cardiovascular disease and worse post-percutaneous coronary intervention outcomes 19 . In stroke, the TyG index has been associated with increased risk of stroke 22 , in-hospital mortality in critically-ill stroke 24 , and early recurrent ischemic lesions 25 . Baseline TyG index has been associated with increased mortality and neurologic deterioration in ischemic stroke 23 .…”
Section: Discussionmentioning
confidence: 99%
“…While the TyG index has demonstrated predictive effects in major adverse cardiovascular event outcomes in patients with acute coronary disease undergoing percutaneous coronary intervention 19 , and was superior to fasting glucose and hemoglobin A1c (HbA1C) in this setting 20 , it has not been well investigated in stroke populations. While previous authors have found an association between incidence of AIS and TyG index 21,22 , limited studies have reported the effect of the TyG index on post-stroke clinical outcomes or recurrence [23][24][25] , and the relationship of the TyG index in a thrombolyzed patient cohort has been studied scarcely. The only two studies that have investigated the effect of IR on AIS patients' response to thrombolysis both utilized HOMA-IR and were limited by sample size or analyzed only non-diabetic patients 26,27 .…”
mentioning
confidence: 99%
“…In addition, subgroup analyses according to the diabetic status of the patients showed similar results. More importantly, a higher TyG index has been associated with the increased risks of early neurological deterioration 37 , early recurrent ischemic lesion 38 , high on-treatment platelet reactivity 39 , and symptomatic intracranial hemorrhage 20 21 in patients with AIS, all of which could lead to the excessive mortality and deteriorated functional outcomes in these patients. Studies are warranted to determine the additional mechanisms underlying the association between TyG index and the prognosis of patients with acute IS.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Therefore, several studies have been conducted so far to prevent the clinical recurrence of ischemic stroke by using ERIL, which is easy to analyze due to its high frequency, as a surrogate marker. 1,4,7 Atherogenic dyslipidemia is a lipid profile represented by high triglyceride, low high-density lipoprotein (HDL) cholesterol, and small/dense low-density lipoprotein (LDL) cholesterol. [8][9][10] These lipoproteins are known to cause various vascular complications including atherosclerosis.…”
Section: Journal Of Neurosonology and Neuroimagingmentioning
confidence: 99%
“…Then, we additionally excluded participants with the following conditions: 1) time delay of >7 days from symptom onset to admission, 2) conducted diagnostic or therapeutic neuro-intervention procedures (n=11), or 3) previous use of lipid-lowering agents before AIP measurements (n=61). 7 Also, as in previous studies dealing with ERIL, we excluded patients with the following stroke mechanisms in consideration of the characteristics of ERIL: 1) small vessel occlusion (n=14), 2) other determined (n=7), and 3) more than two mechanisms (n=4). 7 Finally, a total of 182 AIS patients were included in the final analyses.…”
Section: Study Populationmentioning
confidence: 99%